2014
DOI: 10.15837/ijccc.2012.4.1375
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Discrete-Time Systems with Time-Varying Delay: Delay Decomposition Approach

Abstract: Abstract:This article deals with the problem of obtaining delay-dependent stability conditions for a class of discrete-time systems with interval time-varying delay. Using the decomposition the delay interval into two unequal subintervals by tuning parameter α, a new interval delay-dependent Lyapunov-Krasovskii functional is constructed to derive novel delay-dependent stability conditions which are expressed in terms of linear matrix inequalities. This leads to reduction of conservatism in terms of the upper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…We apply these results to a number of well-studied systems to demonstrate that the notion of intrinsic stability is both computationally inexpensive, relative to other methods, and can be used to improve on some of the best known results. (See for instance Example 4.4, compared to results found in [14,15,16,17,18].) We also show that the asymptotic state of intrinsically stable switched systems is independent of the system's initial conditions (see Main Result 1).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…We apply these results to a number of well-studied systems to demonstrate that the notion of intrinsic stability is both computationally inexpensive, relative to other methods, and can be used to improve on some of the best known results. (See for instance Example 4.4, compared to results found in [14,15,16,17,18].) We also show that the asymptotic state of intrinsically stable switched systems is independent of the system's initial conditions (see Main Result 1).…”
Section: Introductionsupporting
confidence: 55%
“…which satisfies ρ( A ) = 1. Hence this system is not intrinsically stable, even though [14] showed that it is stable for all 0 ≤ L ≤ 9.61 × 10 8 .…”
Section: The Transition Matrix Of the Lifted Representation Ismentioning
confidence: 96%
See 1 more Smart Citation
“…For delayed systems, the most common approaches for characterizing stability are Lyapunov methods, Linear Matrix Inequalities, and Semi-Definite Programming (see, for example, [15,16]. In [10,11] the notion of intrinsic stability was developed as an alternative to these approaches for studying delayed systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, taking an automatic computerbased control system or a process control with networked transmission for example, it is necessary and more reasonable to simultaneously consider the possible transmission delay for the corresponding control law and the device delay due to computing or processing. Recently, much attention has been paid to the subjects of stability, stabilization and control of the time delay systems [1] - [5]. Fractional order models would be more accurate than integer order models.…”
Section: Introductionmentioning
confidence: 99%